Electronic Structure of Copper Corroles. (6th January 2016) - Lemon, Christopher M.; Huynh, Michael; Maher, Andrew G.; Anderson, Bryce L.; Bloch, Eric D.; Powers, David C.; Nocera, Daniel G.
Abstract: The ground state electronic structure of copper corroles has been a topic of debate and revision since the advent of corrole chemistry. Computational studies formulate neutral Cu corroles with an antiferromagnetically coupled Cu II corrole radical cation ground state. X‐ray photoelectron spectroscopy, EPR, and magnetometry support this assignment. For comparison, Cu II isocorrole and [TBA][Cu(CF3 )4 ] were studied as authentic Cu II and Cu III samples, respectively. In addition, the one‐electron reduction and one‐electron oxidation processes are both ligand‐based, demonstrating that the Cu II centre is retained in these derivatives. These observations underscore ligand non‐innocence in copper corrole complexes.